Next generation whole-cell biosensors. Issue 23 (2022) - Fusco, Virginia; Fiore, Davide; di Bernardo, Mario; di Bernardo, Diego
Abstract: Mammalian whole-cell biosensors (WCBs) are cells engineered with biomolecular circuits providing them with ability to sense and report on bioactive molecules, chemicals, or even pathogens (analytes) relevant to human health, that are present within the cell or in the surrounding microenvironment. Applications range from toxicology and drug discovery, to biomanufacturing and biosecurity. Current state-of-the-art whole-cell biosensors are highly dependent on the cell state and have several limitations such as sensitivity to analyte concentration, linear and dynamic range, and robustness to constant disturbances. Here, we introduce two novel designs for whole cell biosensors, based on a feed-forward loop or a negative feedback loop topologies, and perform mathematical modelling and analysis to compare their metrological features against the current state of the art biosensors.